La obediencia a la ley como coraza del pueblo: la defensa de las instituciones jurídicas en el texto del Anónimo de Jámblico - Magoja, Eduardo Esteban (Historia del Derecho, 2021)
One of the main legal principles in ancient Greece was obedience to the law (nomos). Particularly, its importance is based on the fact that it was a central element for the shaping of a harmonious and powerful polis, in which citizens could flourish and lead a happy life. In addition, good legal order was so important that several sources reveal a strong rejection against any such person who, as tyrants, threatens the integrity of political institutions and prioritizes their own interests above anything else. In this regard, the author known as "Anonymous Iamblichus", who is thought to have written in the age of the great Sophists, hypothesizes about the existence of a man of steel (adamantinos aner) to show that no one, no matter how extraordinary and powerful, could live outside the law, justice, and community. This book explores the ethical-political meaning of this argument with the intention of reflecting on the value of laws and their authority. Guided by a methodology that combines a philological analysis and a legal philosophy approach, it seeks to emphasize the richness of Anonymous Iamblichus' text to understand the development process of the supremacy of the law in the history of Athenian democracy.